An evaluation of sleep disturbance on in-patient psychiatric units in the UK. (21st June 2018) - Horne, Sam; Hay, Katherine; Watson, Stuart; Anderson, Kirstie N.
Abstract : Aims and method: Sleep disturbance is common on in-patient psychiatry wards. This study explored subjective and objective patterns of sleep disturbance and contributory environmental factors. Participants were recruited from mental health acute admission wards and had a range of subjective and objective assessments of sleep. Light intensity and noise levels were measured to characterise potential environmental causes for poor sleep. Results: We recruited 20 patients; 15% were high risk for obstructive sleep apnoea. Nineteen participants reported poor sleep quality on the Pittsburgh Sleep Quality Index, and 90% had significant sleep fragmentation with objective measures. Inside light levels were low (day <200 lux and night <10 lux). Night sound levels were 40–90 db. Clinical implications: Sleep disturbance was highly prevalent. Increased awareness of sleep disorders is needed. Modifiable environmental factors on the ward were implicated, therefore increased awareness and a change of approach to sleep disturbance in in-patient psychiatry is recommended. Declaration of interest: None.